METAPLASTIC SQUAMOUS CELL CARCINOMA IN ASSOCIATION WITH INVASIVE LOBULAR BREAST CARCINOMA WITH METASTASIS TO AXILLARY LYMPH NODES - Khan, Mohammad Iqbal; Haque, Anwar ul; Younas, Maliah; Zafar, Afsheen; Shah, Hijab (Journal of Ayub Medical College Abbottabad, 2011)
Squamous cell carcinoma (SCC) of the breast is very rare entity and when encountered it is found in association with invasive ductal carcinoma of the breast. We report a very unusual association of an invasive lobular carcinoma with metaplastic squamous cell carcinoma of the breast which was found not only in a mastectomy specimen but also in the axillary lymph nodes. The patient reported first with a lump breast which was diagnosed a case of invasive lobular carcinoma in a lumpectomy specimen, followed by adjunct radiation and chemotherapy. We encountered such association in only one case report in the literature. Keywords: squamous cell carcinoma, lobular carcinoma, Mastectomy, axillary lymph nodes